PENGARUH SUPERVISE KEPALA RUANG TERHADAP PENINGKATAN KUALITAS INJEKSI INTRAVENA OLEH PERAWAT PELAKSANA - Basuki, Duwi; Purwati, Heni (JURNAL KEPERAWATAN SEHAT, 2014)
Mortality and disability is increasing due to errors in drug administration can prevent with optimum supervision.. The purpose of research to determine the effect of supervision head nurses’ to improve the quality of intravenous drug administration.The study design using pre-experimental design with pre -post approach only one group. Total sample of 40 nurses and 12 head nurses’. Research carried out by dividing the respondents into two groups: the treatment group and the control group. The treatment group was given training supervision then evaluated the implementation of the supervision and implementation of intravenous drug administration by nurses. The control group did not receive treatment.Results showed the group given supervision increased 25.25 points in the implementation of intravenous drug administration. Whereas the control groupthere was no increase. The results of statistical tests significant effect training supervision to improve the quality of intravenous drug administration proved by value (p = 0.000, α = 0.05).Efforts to improve the quality of intravenous injection with the application of supervision, supervision scheduling, and provide training supervision and training of injection techniques regularly.Keywords:Training, supervision head Nurse’s, quality, drug administration, intravenous